Border handling as the most correct dynamic principle of the beginning of the register of immovable cultural heritage development - Chabaniuk, V.; Dyshlyk, O.; Polyvach, K.; Pioro, V. (Land Management, Cadastre and Land Monitoring, 2021)
The correct start of work on developing a spatial data infrastructure of the domain of immovable cultural heritage (CH) of Ukraine is to model the entities boundaries of the CH in the most accessible way at the moment. Created models are used together with the necessary transformations, both in separate systems from the set of CH domain systems, and in several appropriately ordered systems from this set. Many of the required systems are organized into a hierarchy of systems called Atlas Geographic Information System: from public models of CH entities on the Internet to the State System for permanent registration or registration of CH objects under the Ministry of Culture and Information Policy (MCIP) of Ukraine. Border management includes support for the entire life cycle of the spatial characteristics of CH entity models – from random statement about the CH object to the transformation into an object of the registration system or even an object of the national register. It is shown that when defining boundaries, you need to be able to work with different spatial characterizations of the CH object. It is proved that this characterization can be started from available cartographic material, and not from the implementation of land management projects, as it is done in the case of spatial characterization of land parcels. The elements of the methodology are described, which allows to carry out the necessary spatial characterization of the CH objects in practice. Key words: spatial characterization of immovable cultural heritage objects, NSDI, methods of border management, relational cartography, conceptual framework, solutions framework.